2018
DOI: 10.1007/s10803-018-3524-y
|View full text |Cite
|
Sign up to set email alerts
|

Early Identification of ASD Through Telemedicine: Potential Value for Underserved Populations

Abstract: Increasing access to diagnostic services is crucial for identifying ASD in young children. We therefore evaluated a telemedicine assessment procedure. First, we compared telediagnostic accuracy to blinded gold-standard evaluations (n = 20). ASD cases identified via telemedicine were confirmed by in-person evaluation. However, 20% of children diagnosed with ASD in-person were not diagnosed via telemedicine. Second, we evaluated telediagnostic feasibility and acceptability in a rural catchment. Children (n = 45)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
135
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 99 publications
(147 citation statements)
references
References 37 publications
10
135
0
2
Order By: Relevance
“…In addition to benefits of tele-assessment, providers identified several key barriers, with all providers endorsing technology-related challenges in their tele-assessment visits. This is a finding consistent with prior research on telehealth-delivered services (Juárez et al 2018 ). Families were unfamiliar with the required technology (software requirements, apps) and often had difficulty navigating the EMR system to begin the visit or access their evaluation reports.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition to benefits of tele-assessment, providers identified several key barriers, with all providers endorsing technology-related challenges in their tele-assessment visits. This is a finding consistent with prior research on telehealth-delivered services (Juárez et al 2018 ). Families were unfamiliar with the required technology (software requirements, apps) and often had difficulty navigating the EMR system to begin the visit or access their evaluation reports.…”
Section: Discussionsupporting
confidence: 92%
“…Though feasibility and acceptability are important first steps, rigorous empirical evaluation on the accuracy and effectiveness of these innovative methods is critical. Prior work has demonstrated that many young children with ASD can be accurately identified using clinic-based tele-assessment procedures (Juárez et al 2018 ), but it is unclear how diagnostic accuracy varies within direct-to-home care. With regards to the TELE-ASD-PEDS, there is currently a large study underway examining the psychometric properties of the tool relative to traditional, gold-standard evaluations (1R21MH118539-01), and initial data support the diagnostic accuracy of the TELE-ASD-PEDS when implemented in a laboratory setting (Corona et al 2020b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Domenech Rodríguez, 2009;Juárez et al, 2018;Kaonga & Morgan, 2019;Langdon, 2009;Stahmer et al, 2019].…”
Section: Closing Down Our Research Programs In Bostonunclassified
“…Multiple cultural, linguistic, and socioeconomic factors affect when and if individuals in Spanish-speaking households access quality ASD care, including: differences in parenting views, availability of Spanish-speaking providers, transportation or employment challenges, access to information about ASD, and health insurance coverage [Stahmer et al, 2019]. Telehealth models for ASD offer promising solutions for closing the gap faced by Latino families, gaps that are now intensified by COVID-19 [Juárez et al, 2018]. As more professionals adopt telehealth, the research community has an opportunity to strengthen this tool for Latino families of children and adults with ASD.…”
mentioning
confidence: 99%